READING ANXIETY OF EFL LEARNERS IN INDONESIAN RURAL SCHOOLS: A QUANTITATIVE STUDY - Mudra, Heri; Mckinnon, Timothy (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2022)
The purposes of this current study were twofold. First, it attempted to find out the level of reading anxiety among EFL learners in rural schools. Second, it sought to determine whether there is a statistical difference in reading anxiety between rural EFL learners across gender and level of study. Seventy-seven EFL learners from several rural Indonesian schools were involved in completing a 27-items EFL Reading Anxiety Inventory (EFLRAI). The findings revealed different levels of top-down, bottom-up, and classroom reading anxiety among rural school learners. Regarding the statistical differences across gender, it is found that male learners outperformed females in terms of top-down and bottom-up reading anxiety. However, female learners offered a better understanding than male learners. Meanwhile, in terms of study grades, it is stated that freshmen learners are more dominant in experiencing reading anxiety than junior and senior learners. In short, reading anxiety has different levels among different EFL learners. In addition, differences occur when each learner with different gender and study grade experience anxiety in reading.